Perancangan Web E- Commerce Berbasis Website pada Toko Ida Shoes - Muhamad Dody Firmansyah; Herman Herman (Journal of Information System and Technology (JOINT), 2023)
Online shopping has recently shown a very rapid development and plus there is a deadly virus that makes people afraid to leave the house, so an alternative way to not have to leave the house is to shop online. With the passage of time, there has been a change in shopping, where you usually have to go to the place directly, now you don't have to go directly to the place of shopping because of the existing technology. So with more and more people buying things online, the e-commerce site must look good and be easy to use. This research was conducted to design a website-based E-commerce design to make it more attractive. Making this research using data collection